Innovative systems for the detection of air particles in the quarries of the Western Rif, Morocco - Fattah, Ghizlane; Mabrouki, Jamal; Ghrissi, Fouzia; Elouardi, Mohamed (International Journal of Reconfigurable and Embedded Systems (IJRES), 2024)
In a world where climate change looms large the spotlight often shines on greenhouse gases, but the shadow of man-made aerosols should not be underestimated. These tiny particles play a pivotal role in disrupting Earth's radiative equilibrium, yet many mysteries surround their influence on various physical aspects of our planet. The root of these mysteries lies in the limited data we have on aerosol sources, formation processes, conversion dynamics, and collection methods. Aerosols, composed of particulate matter (PM), sulfates, and nitrates, hold significant sway across the hemisphere. Accurate measurement demands the refinement of in-situ, satellite, and ground-based techniques. As aerosols interact intricately with the environment, their full impact remains an enigma. Enter a groundbreaking study in Morocco that dared to compare an internet of thing (IoT) system with satellite-based atmospheric models, with a focus on fine particles below 10 and 2.5 micrometers in diameter. The initial results, particularly in regions abundant with extraction pits, shed light on the IoT system's potential to decode aerosols' role in the grand narrative of climate change. These findings inspire hope as we confront the formidable global challenge of climate change.